Improved Vectors for Selecting Resistance to Hygromycin - Anne M. Carroll; James A. Sweigard; Barbara Valent (Fungal Genetics Reports, 1994)
Resistance to hygromycin B is an important dominant selectable marker in fungal transformation. Our goal was to improve vectors for hygromycin selection by making the gene more compact, by eliminating sites for commonly used restriction enzymes, and by subcloning the modified gene into convenient vectors. These improvements were made by modifying pCSN43 (Staben et al. 1989 Fungal Genetics Newsl. 36:79-81) through three rounds of megaprimer mutagenesis (Aiyar and Leis, 1993 Biotechniques 14:366-368 ), a technique based on polymerase chain reaction amplification. Plasmid pCSN43 has a 2.4 kb SalI fragment containing the bacterial hph gene (Gritz and Davies, 1983 Gene 25:179-188), encoding hygromycin B phosphotransferase, under control of the Aspergillus nidulans trpC promoter and terminator (Mullaney et al. 1985 MGG 199:37-45)